Implementasi Kebijakan Pemerintah Tentang Penerimaan Peserta Didik Baru Berdasarkan Sistem Zonasi Di Indonesia - Alma Oktafiana; Yolanda Fitria Laksanti; Dian Suluh KD (Jurnal Ilmu Politik dan Pemerintahan, 2019)
Admission of new students (PPDB) is an education system as a selection process for prospective new students who will enter the higher education level, which is organized by each level of the formal education unit. The PPDB implementation process is carried out under the supervision of the Education Office, while the implementation is the respective education unit. The zoning system policy has been running for two years, since the enactment of PERMENDIKBUD NO. 14 of 2018 concerning the acceptance of new students. In this regard the government hopes to eliminate the stigma of favorite schools, equalize educational services, provide opportunities for schools that are not favorites to process superior. The method used in this study is a qualitative research method with a research focus on how the implementation of government policies regarding the acceptance of new students based on the zoning system in Indonesia. Data sources obtained from a collection of several articles on the internet and book sources by way of study to the library using internet access methods. The collected data is then analyzed using the content analysis method.